Pajak Iklan Online - Maria Emelia Retno Kadarukmi (Syntax Corporation Indonesia, 2024)
This paper sheds new light on the question of how to build a tax model for online advertising and digital companies. Policy measures to tax transnational companies, including digital companies, should be based not only on the question of where and how much value is generated, but also on the question of who generates how much value. The legal definition of ‘digital permanent enterprise’ used in the context of online company taxation should be built on the understanding that only human labor creates the economic value of commodities. To counter the dominance of non-profit monopoly platforms on the Internet, the creation of public Internet services is a viable policy option. Introducing an online advertising tax is an ideal financial foundation to support the creation of public service Internet platforms and civil society Internet platforms.